Dinamika Dan Fungsi Kepemimpinan Pendidikan - Hasan basri; Muhammad syaifudin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of writing this paper is to describe the dynamics of leadership, leadership functions and the role of leaders to improve the quality of education in the context of global challenges. In preparing this work using the literature review method. Documents as a reference for the author in extracting data as well as several previous works. Descriptive analysis as a reference in analyzing and describing the work. The result of this work is that educational leadership by school principals requires effective leadership skills and an understanding of the dynamics of stakeholder interactions to achieve optimal learning goals and quality educational experiences. The function of leadership in education is to optimize the involvement of all parties, create a dynamic and comfortable school environment, and face global challenges through the functions of instruction, consultation, participation, delegation and control. School leaders have a key role in improving the quality of education through setting high quality standards, responding to consumer preferences, creating an inclusive environment, ensuring the availability of resources, and influencing the quality of educational processes and outputs by being leaders who are dependable, accepted, and always present when needed.